Mitigation of residual stress and deformation induced by TIG welding in thin-walled pipes through external constraint - Yong Liu (Elsevier, 2021)
Thin-walled pipes have been widely used in chemical facilities and propulsion structures, where the distortion problem induced by welding fabrication is common and prominent, deteriorating assembly accuracy and even reducing load-bearing capacity. External constraint has shown great capacity to control the residual stresses and welding deformation. The objective of this research is to investigate the effect of constraint on welding process in thin-walled 304 stainless steel pipes through experiments and numerical simulation. To include the clamping effect in the welding simulation, the external constraint was modeled as the additional heat dissipation and mechanical restraint. The seam welded pipes with and without constraints were both modeled for comparison purpose. Good agreement was obtained between numerical modeling and measurements in both pipes. The results show that the welding deformation and residual stresses are both obviously reduced under the effect of external constraint, which was found to work mainly in the cooling process by generating more tensile plastic strain so as to reduce the shrinkage force in both axial and hoop directions. The maximum distortion is observed on the middle section of constrained pipe and on the end sections in the unconstrained one, which is caused by the combined effect of bending direction on the circumference and shrinkage force in the axial direction according to the inherent strain analysis. Moreover, the analysis of welding deformation mode reveals that the inward bending induced by hoop constraint contributes to the dimensional accuracy of the pipe ends under axial shrinkage forces. Parametric simulation analysis of the external constraint strategy was performed, and the results showed that reducing the constraint distance was the most effective way to mitigate welding distortion in seam welded pipes.